A Christmas present worth having - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | When the casino resorts applied for the first licenses to operate in Macau, one of the commitments that they made was to serve the Macau society. Many of them have honoured those commitments outstandingly well, and continue to do so, and in ways too many and diverse to list here.
Section: Macau Business